HIGHER EDUCATION TEACHER’S DIGITAL VIDEO BRAND FORMATION: TECHNICAL ASPECTS - Valerii Lymarenko (Неперервна професійна освіта: теорія та практика)
The article examines the technical aspects of a higher education teacher’s digital video brand formation as one of the key tools for effective communication with students in the context of the digital transformation of education and the spread of distance learning. The importance of educational video content for improving the quality of educational interaction, expanding the audience, increasing students’ engagement, and strengthening the professional image of teachers is substantiated. It has been established that educational video content not only performs a didactic function but also plays an important role in shaping the professional image and increasing the recognition of the teacher, expanding the target audience, and ensuring flexibility and personalisation of learning. The author’s definition of the concept of “digital video brand of a higher education institution teacher” is presented. It is a component of the teacher’s personal brand, which is implemented in the educational video content created by the teachers, representing their professional competence, pedagogical individuality and values in the digital environment and contributing to the strengthening of the academic image of both the teacher and the higher education institution. The structural components of the formation of a digital video brand of a higher education institution teacher have been identified: a personality, content, and a platform. The technical aspects of designing educational videos have been analysed: image and sound quality, duration, recording format, recording and editing services, as well as the choice of a platform for publishing content. The obtained results can be used as a basis for further research in the field of personal branding in education, pedagogical video production, digital communication, and media didactics.